I need to publish more and read less! How new platforms will enable you to publish more effectively while reducing information overload - Neylon, Cameron (Septentrio Conference Series, 2014)
The pressure on researchers to generate publications is increasing and the competition for increasingly scarce resources is bringing this pressure to critical levels. At the same time the web creates new opportunities to communicate, both to other researchers through sharing of things beyond the traditional journal publication, and to the wider community through lower costs of distribution. This is both a benefit, bringing opportunities for new forms of publication and reducing the costs of sharing research outputs like data, software, and research records, and also a burden, as it brings new expectations of the availability of information. The result of these pressures is an explosion of information which challenges our ability to cope. Looking ahead, how can we shape the way that we communicate, and the way that we discover information? What is the optimal design for a system that communicates research effectively and efficiently while allowing researchers to focus on their research?